The Influence of Student Perception, Interest, and Trust on the Role of Sharia Investment Gallery - Nilam Cahya Ary Santika; Deny Yudiantoro; Amalia Nuril Hidayati (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The Student Investment Gallery provides a place for students to invest which can later grow their perception, interest, and trust in investing. The purpose of this study is to find out the role of the Islamic Investment Gallery which can affect perceptions, interest, and trust in investing. The method in this study uses quantitative. The role of the Sharia Investment Gallery has been optimal or not for the implementation of student investment in the campus environment. The sample in this study used a purposive sampling technique and was calculated using the Slovin formula with an error rate of 10% in determining the sample quantity. Data collection techniques in this study used questionnaires. The source of the data in this study was primary data, totaling 90 respondents from students of the Islamic Financial Management Study Program class of 2019-2021. The data that has been collected is then tested using SPSS, namely testing several tests which include the reliability test, data normality test, multicollinearity test, heteroscedasticity test, T-test, and F test. on the role of the Sharia Investment Gallery. Partially, the student interest variable (X2) influences the role of the Islamic Investment Gallery. Partially, the student trust variable (X3) influences the role of the Islamic Investment Gallery.